Short communication: Paclobutrazol for height control of two Lilium L.A. hybrids grown in pots - Francescangeli, N.=700 1 Marinangeli, P.; Curvetto, N.
(En, Es)
Ilus., 15 ref.
Keywords: LILLIUM; ENANISMOS; CONTROL QUIMICO; INMERSION; BULBOS; PACLOBUTRAZOL; INHIBIDORES DEL CRECIMIENTO; SUSTANCIAS DE CRECIMIENTO VEGETAL; ESPAÑA